2017
DOI: 10.1080/08927014.2017.1310848
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bacterial contaminants from calcium carbonate filler production lines and an evaluation of biocide based decontamination procedures

Abstract: The aim of this study was to analyze the bacterial community in the production line of a calcium carbonate filler production company and to investigate possible causes for bacterial presence. Throughout 2012, 24 carbonate slurry and six groundwater samples were analyzed. Pseudomonas and Microbacterium were the most frequent contaminants in the slurry, whereas Pseudomonas and Brevundimonas dominated the groundwater samples. Of the 43 different bacterial strains isolated, only five were found both in the slurry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…granulorum is a bacterium first isolated in aerobic granules, a recent innovation in biological wastewater treatment, with the ability to be exposed to high organic loading rates [45]. The analysis of the bacterial community in the production line of a calcium carbonate filler company showed that Pseudomonas and Microbacterium were the most frequent contaminants in the slurry [52]. After biocidal treatment, resistance development was highlighted [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…granulorum is a bacterium first isolated in aerobic granules, a recent innovation in biological wastewater treatment, with the ability to be exposed to high organic loading rates [45]. The analysis of the bacterial community in the production line of a calcium carbonate filler company showed that Pseudomonas and Microbacterium were the most frequent contaminants in the slurry [52]. After biocidal treatment, resistance development was highlighted [52].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the bacterial community in the production line of a calcium carbonate filler company showed that Pseudomonas and Microbacterium were the most frequent contaminants in the slurry [52]. After biocidal treatment, resistance development was highlighted [52]. Studying the interactions among four bacterial species, including M. saperdae, capable of degrading an industrial coolant and lubricant also containing biocides, Piccardi et al [53] found only positive or neutral interactions among the taxa.…”
Section: Discussionmentioning
confidence: 99%